Toward Integrated Urban Observatories: Synthesizing Remote and Social Sensing in Urban Science - Danlin Yu (Remote Sensing)
Urbanization is reshaping landscapes and posing unprecedented sustainability challenges, necessitating more integrative approaches to urban observation. This review synthesizes recent advancements in traditional remote sensing and emerging social sensing technologies, emphasizing their convergence within urban science. A systematic thematic analysis of 667 peer-reviewed articles highlights the methodological progress, practical applications, and theoretical innovations arising from this integration. Traditional remote sensing effectively captures urban physical features but lacks insights into human behaviors. Conversely, social sensing, leveraging digital traces from social media and mobile data, introduces essential human-centered dimensions into urban monitoring. The fusion of these complementary paradigms through advanced data analytics and multimodal integration has produced transformative methodologies, enhancing urban resilience frameworks, functional zone delineation, and real-time disaster responses. Despite significant progress, the integration faces persistent challenges, including data heterogeneity, representational bias, ethical concerns, and scalability limitations. Differing from previous reviews that survey the landscape, the current work argues that current integration efforts remain ad hoc and technologically driven, lacking a unifying theory for real-time urban governance. To address this critical gap, I develop and operationalize a new systems-based framework for hybrid urban observatories. This framework is built on a socio-ecological foundation and explicitly integrates technical components with an essential governance layer, advancing both methodological rigor and actionable guidance for the field. Such a framework will enable a more holistic, responsive, and equitable approach to urban governance and sustainability.